Overcoming the “Coloniality of Doing” in International Law: Soft Law as a Decolonial Tool - Tatiana Cardoso Squeff (Revista Direito GV)
Abstract Law, as a set of norms designed to regulate social life, is a field of difficult change, being always behind its time. The case of international law is even harder due to the limits of its positivist normative structure, formulated not only by countries that hold military/economic power in the international arena, but also in a modern/colonial historical moment that has guaranteed their legitimacy for more than five centuries, which makes it extremely difficult to have rules that contemplate the desires of the Third World. Thus, what seems to exist is that, in addition to the colonialities of power, knowledge and being, there is also the “coloniality of doing”, limiting the development of international rules. Hence, this paper addresses this problem, since the existing norms have a high coloniality burden and will hardly be altered by the current formulas. To this end, by following an explanation of decolonialism as an epistemic approach and its relation to the Third World Approaches to International Law (TWAIL), the role of soft law will be addressed as a decolonial tool capable of solving the existing impasse. Based on the deductive method and a critical-explanatory approach, an applied research will be conducted using the bibliographic procedure for analysis with qualitative selection.